Social Inequalities in Palliative Care for Cancer Patients in the United States: A Structured Review - Elk, Ronit (Semin Oncol Nurs, 2018)
OBJECTIVES: To identify patterns of access to and use or provision of palliative care services in medically underserved and vulnerable groups diagnosed with cancer. DATA SOURCES: Google Scholar, PubMed, MEDLINE, and Web of Science were searched to identify peer-reviewed studies that described palliative care in medically underserved or vulnerable populations diagnosed with cancer. CONCLUSION: Disparities in both access and referral to palliative care are evident in many underserved groups. There is evidence that some groups received poorer quality of such care. IMPLICATIONS FOR NURSING PRACTICE: Achieving health equity in access to and receipt of quality palliative care requires prioritization of this area in clinical practice and in research funding.